2015
DOI: 10.1590/1519-6984.01014
|View full text |Cite
|
Sign up to set email alerts
|

Is otolith microchemistry (Sr: Ca and Ba:Ca ratios) useful to identify Mugil curema populations in the southeastern Caribbean Sea?

Abstract: The aim of the present study was to evaluate the potential use of otolith microchemistry (Sr:Ca and Ba:Ca ratios) to identify silver mullet, Mugil curema, populations in Southeastern Caribbean Sea. Fish samples were collected in 7 areas of Nueva Esparta State (Venezuela). The otolith Sr:Ca and Ba:Ca ratios and water Sr:Ca were determined (by ICP-OES and EDTA volumetric method). Otoliths Sr:Ca and Ba:Ca ratios and Sr:Ca partition coefficient of mullets in Cubagua island (south of the State) were significantly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 32 publications
(45 reference statements)
0
14
0
4
Order By: Relevance
“…In this context, Avigliano et al (2015) evaluated the potential use of otolith microchemistry (Sr ÷ Ca and Ba ÷ Ca ratios) to identify the silver mullet, Mugil curema Valenciennes, 1836, populations in the south-eastern Caribbean Sea. In fact, the authors mentioned above, observed the existence of different groups of in this geographic area.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Avigliano et al (2015) evaluated the potential use of otolith microchemistry (Sr ÷ Ca and Ba ÷ Ca ratios) to identify the silver mullet, Mugil curema Valenciennes, 1836, populations in the south-eastern Caribbean Sea. In fact, the authors mentioned above, observed the existence of different groups of in this geographic area.…”
Section: Discussionmentioning
confidence: 99%
“…The morphometrical study of these structures allows one to describe and compare their shapes quantitatively (Lestrel, ). Moreover, the use of Sr/Ca and Ba/Ca otolith ratios has been simultaneously studied by some authors as indicators of habitats, and for stock and migration studies (Avigliano, Callicó Fortunato, Buitrago, & Volpedo, ; Schuchert, Arkhipkin, & Koenig, ; Tabouret et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…La relación Ba/Ca no presentó diferencias significativas entre los bordes de los otolitos de peces de los tres humedales. Como se mencionó previamente, la concentración de Sr en otolitos correlaciona positivamente con la salinidad de agua frecuentada por el pez (Kraus y Secor, 2004;Sturrock et al, 2012), mientras que los valores de Ba correlacionan negativamente con la salinidad o conductividad de las masas de agua circundante (Elsdon y Gillanders, 2005;Tabouret et al, 2010;Miller, 2011;Avigliano et al, 2015c). Los resultados obtenidos evidencian que la relación Sr/Ca de los otolitos fue una variableútil para diferenciar peces que frecuentanáreas de mayor salinidad, como sucede con SP (posee una salinidad de 37,3 UPS) en relación a los otros humedales estudiados.…”
Section: Discussionunclassified
“…Además, Radtke y Shafer (1992) han sugerido que la composición química de los otolitos está regulada por la actividad fisiológica de los peces, que a su vez está influenciada por las condiciones ambientales. La morfometría y la microquímica de los otolitos han ayudado a la identificación de stocks de gran número de especies comerciales (Tuset et al, 2003b;Gillanders, 2005;Tracey et al, 2006;Tabouret et al, 2010;Avigliano et al, 2014;Avigliano et al, 2015c;Avigliano et al, 2015e;Sadighzadeh et al, 2014). El estudio de la forma y contorno del otolito ha permitido, también, identificar especies de una misma familia (Tuset et al, 2003a;Lestrel, 2008;Avigliano et al, 2015a).…”
Section: Introductionunclassified
See 1 more Smart Citation